Inverse salt sensitivity: an independent risk factor for cardiovascular damage in essential hypertension. Issue 8 (August 2022) - Cuka, Ermira; Simonini, Marco; Lanzani, Chiara; Zagato, Laura; Citterio, Lorena; Messaggio, Elisabetta; Faienza, Sipontina; Brioni, Elena; Hamlyn, John M.; Manunta, Paolo
Abstract : Objective: Salt sensitivity is a powerful risk factor for cardiovascular (CV) disease and mortality in both normotensive and hypertensive patients. We investigated the predictive value of the salt sensitivity phenotype in the development of CV events and hypertensive target organ damage (TOD) among essential hypertensive patients. Methods: Eight hundred forty-four naive hypertensive patients were recruited and underwent an acute saline test during which blood pressure (BP) displayed either no substantial variation (salt-resistant, SR individuals), an increase (salt-sensitive, SS), or a paradoxical decrease (inverse salt-sensitive, ISS). Sixty-one patients with the longest monitored follow-up (median 16 years) for blood pressure and organ damage were selected for the present study. A clinical score for TOD development based on the severity and the age of onset was set up by considering hypertensive heart disease, cerebrovascular damage, microalbuminuria, and vascular events. Results: CV events were significantly higher among SS and ISS than in SR patients. The relative risk of developing CV events was 12.67 times higher in SS than SR and 5.94 times higher in ISS than SR patients. The development of moderate to severe TOD was 10-fold higher in SS and over 15-fold higher in ISS than in SR patients. Among the three phenotypes, changes in plasma endogenous ouabain were linked with the blood pressure effects of saline. Conclusions: Salt sensitivity and inverse salt sensitivity appear to be equivalent risk factors for CV events. The response to an acute saline test is predictive of CV damage for newly identified ISS individuals. Abstract :